Sistem Inventory Berbasis Cloud Enterprise Resource Planning Menggunakan ODOO 16 - Swastika , Rahayu; Daniel , Daniel; Ariyati , Indah (Journal of Students‘ Research in Computer Science, 2023)
Competition between is increasing including in retail trade. With the rapid development of technology, retail needs to be more responsive. Retailers must be able to run their business efficiently if they want to compete with global. This is due to the fact that many traditional retailers start opening contemporary retail stores, such as Aneka Furniture. Enterprise Resource Planning (ERP) is a method that can be used to integrate existing systems in an enterprise. ERP divides information into two parts, that is, within and between business processes, and running a business digitally. ODOO is an Enterprise Resource Planning software that can be used as an enterprise system that can integrate existing systems in the company. The research used the Inventory Module and found that some ODOO software features, such as product input, receipt input, shipment and return, and report printing, were used. It is expected that this research will help inventory recording in Aneka Furniture.